Exosome-inhibiting polymeric sonosensitizer for tumor-specific sonodynamic immunotherapy - Wu, Jiayan (2024)
Combination cancer immunotherapy based on electromagnetic energy and immunotherapy shows potent anti-cancer efficacy. However, as a factor that mediates tumor metastasis and immune suppression, the impact of tumor exosomes on therapy under electromagnetic energy stimulation remains unclear. Herein, findings indicate that sonodynamic therapy (SDT) increases serum exosome levels by inducing apoptotic exosomes and loosening the tumor extracellular matrix, promoting lung metastasis. To address this problem, an exosome-inhibiting polymeric sonosensitizer (EIPS) selectively inhibiting tumor exosome generation in response to the tumor biomarker is synthesized. EIPS consists of a semiconducting polymer backbone capable of inducing SDT and a poly(ethylene glycol) layer conjugated with a tumor-specific enzyme-responsive exosome inhibitor prodrug. After being cleaved by tumor Cathepsin B, EIPS releases active exosome inhibitors, preventing tumor exosome-mediated immune suppression and lung metastasis. As a result, EIPS elicits robust antitumor effects through the synergistic effect of SDT and tumor exosome inhibition, completely preventing lung metastasis and establishing a long-term immune memory effect. This is the first example showing that combining SDT with tumor-specific exosome inhibition can elicit a potent immune response without the help of typical immune agonists.